(3eNJUQ CUd YdGA Hf QRjfs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3eTgO CejQ GdeDefjf Ydj Hf CHj WGdHs)
(3ChdgG (B:s
(3HSe Gddg (B... (3Yf CHj LYaQ Ydjg GdSdGe aj bhdg JYGdi hdbO BJjfGc SHYG ef GdeKGfj hGdbQBf GdYXje bGd BjI GdcQSj Yf eMeO Hf eSde Yf CHj LYaQ Ydjg GdSdGe bGd cGf CHj Ydj Hf GdMSjf jSCdfG (B...s
(3BNQgG (B:s
.. (3eMeO Hf eSde bGd SCdJg Yf GdUdGI Ydi GdejJ bGd JHOC hJUdj Ydi GdfHj Udi Gddg Ydjg hSde aEfg CMb GdehJi Cf jUdi Ydjg hGOY dfaSc hGdeDefjf hGdeDefGJ (B..(3BNQ GdeNJGQs
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\109s
(3GdPQjYI (B20 - 120 ( 2481 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs